2011
DOI: 10.1007/s10722-011-9772-8
|View full text |Cite
|
Sign up to set email alerts
|

Extending the rapeseed genepool with resynthesized Brassica napus L. I: Genetic diversity

Abstract: Resynthesized Brassica napus L. could be employed to increase the genetic variation in the narrow oilseed rape genepool and to establish a genetically distant genepool for hybrid breeding. One important criterion for selecting appropriate resynthesized lines is their genetic distance to adapted breeding material. In this study we estimated the genetic distances in a wide collection of 142 resynthesized lines and 57 winter and spring rapeseed cultivars from Europe, North America and Asia using RFLP marker data.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
34
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(35 citation statements)
references
References 23 publications
(18 reference statements)
0
34
0
1
Order By: Relevance
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have demonstrated the value of utilizing allelic diversity of the allied Brassica species for increased heterosis in B. napus (Qian et al, 2005;Li et al, 2006;Zou et al, 2010;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013;Li et al, 2014). For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata.…”
mentioning
confidence: 99%
“…For example, Zou et al (2010) observed a high level of heterosis in test hybrids while using germplasm diversified with the A genome of B. rapa and the C genome of B. carinata. A number of researchers have also utilized genetic diversity of resynthesized B. napus (from B. rapa × B. oleracea interspecific cross) for the improvement of openpollinated or hybrid winter B. napus cultivars (Gehringer et al, 2007;Radoev et al, 2008;Girke et al, 2011Girke et al, , 2012Jesske et al, 2013). Udall et al (2006) detected two QTL, where the allele from a resynthesized B. napus increased seed yield of spring B. napus.…”
mentioning
confidence: 99%
“…Molecular analyses of 94 B. napus accessions performed in this study did not surprisingly confirm assumptions about the narrow genetic base of rapeseed core collection (Girke et al 2012). Such an assumption is correct only if restricted sets of oilseed rape are analysed (e.g.…”
Section: Discussionmentioning
confidence: 55%
“…The genetic base of oilseed rape (Brassica napus) is quite narrow due to its limited geographic range and intensive breeding (Girke et al 2012). Research on Brassica germplasm and evaluation of its genetic diversity could accelerate the efficient use of genetic variation through establishing a breeding programme (Stokes et al 2010;Harper et al 2012).…”
mentioning
confidence: 99%
“…Indeed, more than 50% of the Chinese B. napus cultivars are derived from B. napus )B. rapa interspecific crosses (Liu 1985, cited by Chen et al 2008. Furthermore, some researchers have also utilized the genetic variability of B. rapa and B. oleracea through the use of resynthesized B. napus lines, created from these two diploid species, to improve a specific trait (Chen et al 1988;Akbar 1989;Rahman 2001Rahman , 2004 or to broaden genetic diversity (Becker et al 1995;Girke et al 2011Girke et al , 2012 in oilseed B. napus. Conversely, very little effort has been made to utilize the genetic diversity of B. oleracea for the improvement of B. napus through crosses between B. napus and B. oleracea.…”
mentioning
confidence: 99%